African healing shrines and cultural psychologies - Michael, Matthew; Danfulani, Umar Habila Dadem (Regnum studies in mission., 2020)
This book presents a pioneering work on the ethnopsychology of African healing spaces and its strategic influence in the contemporary constructs and negotiations of African sacred geography. Since African Christianity towers now-as the "new global face" of World Christianity-and the defining face of the "Next Christendom", there is the urgent need to engage the active conversations of African Christianity in direct relationship to the larger therapeutic background of African healing shrines